2012
DOI: 10.1063/1.4752866
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery of light-induced degradation on the micromorph solar cells by electric field

Abstract: The recovery of light-induced degradation of the tandem micromorph solar cell by applying reverse bias is compared with the single-junction amorphous silicon solar cell. The illuminated current density-voltage characteristics and external quantum efficiency show that the degradation of both the micromorph and the amorphous silicon cells can be recovered by applying sufficient reverse bias. The micromorph cell was recovered at smaller reverse bias than amorphous silicon cell. The abundant H in the microcrystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…We cannot draw any definite conclusion about the nature of such charged defect species, but we speculate it may be related to alkaline metal or hydrogen ions (as suggested in Ref. [9]), which are well known to be able to rapidly diffuse and migrate under electric field application in SiO 2 , and most likely also in FTO and in glass. The results (almost no effect of reverse bias stress under illumination) seen in a-Si:H solar cells fabricated exactly in the same way but on Mo substrates rather than on FTO/glass substrates confirm the above idea and suggest that these charged defects are exchanged with the FTO/ glass.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…We cannot draw any definite conclusion about the nature of such charged defect species, but we speculate it may be related to alkaline metal or hydrogen ions (as suggested in Ref. [9]), which are well known to be able to rapidly diffuse and migrate under electric field application in SiO 2 , and most likely also in FTO and in glass. The results (almost no effect of reverse bias stress under illumination) seen in a-Si:H solar cells fabricated exactly in the same way but on Mo substrates rather than on FTO/glass substrates confirm the above idea and suggest that these charged defects are exchanged with the FTO/ glass.…”
Section: Resultsmentioning
confidence: 94%
“…The authors suggested that their findings might be due to field emission of either electrons or holes from the metastable defects rendering these defects charged and therefore mobile or to hydrogen ion motion, possibly on the internal surfaces of micro voids. In a recent report it was shown that in micromorph solar cells the required reverse bias for solar cell partial recovery after light soaking is less than that of single-junction a-Si cell, and that the microcrystalline Si bottom cell acts as a hydrogen reservoir, indicating the crucial role played by H to passivate the defects responsible for a-Si:H cell degradation after light soaking [9]. In this work we show that the application of a strong electric field in reverse bias not only slows down the solar cell ageing kinetics but also even produces an improvement of the cell parameters as a function of stress time.…”
Section: Introductionmentioning
confidence: 98%